'A public key infrastructure model for privacy‐enhancing general purpose eIDs'. Issue 2 (1st March 2015) - Kefallinos, Dionysis; Sykas, Efstathios
Abstract : In this study, the authors propose a hybrid identity certificate – attribute certificate public key infrastructure (PKI) model with elements of anonymity, applicable to general purpose electronic identities, which aims to defend personal information privacy, hinder user tracking and preserve the free will of its users. The authors analyse the associated processes, the certificate contents and the roles of the parties involved. The authors' motive for its formulation is the belief that research previously done in this field is either too restrictive, too proprietary, too difficult to implement, or a combination of the above. In addition, the PKIs that have been deployed in most countries, both public and private, do not in the authors view protect personal information privacy. Instead, the authors propose a model that adheres to standards, is easy to implement, requires as little as possible application development for integration into commercial PKI systems, is suitable for large‐scale deployment and concedes little in the protection of personal information privacy.